Pengaruh Model Pembelajaran Berbasis Masalah Berbantuan PhET Terhadap Kemampuan Pemecahan Masalah Momentum dan Impuls Peserta Didik Kelas XI - Nia Rizki Kurniawati; Ni Nyoman Sri Putu Verawati; Ahmad Harjono (Lensa: Jurnal Kependidikan Fisika, 2026)
This study examined the effect of PhET-assisted problem-based learning on students’ problem-solving ability in momentum and impulse. A quasi-experimental method with a pretest-posttest control group design was used. The participants were 57 eleventh-grade students at SMAN 1 Lembar, consisting of 29 students in the experimental class and 28 students in the control class. The experimental class learned through problem-based learning assisted by PhET simulations, whereas the control class received conventional instruction. Data were collected using six validated and reliable essay items measuring four indicators of problem-solving ability: recognizing the problem, planning a strategy, applying the strategy, and evaluating the solution. The results showed that the experimental class achieved a higher posttest mean score (86.11) than the control class (78.17). The independent-samples t-test indicated a significant difference between groups, t(55) = 2.13, p = .038, confirming the effect of the intervention. The N-Gain score of the experimental class was 0.81, categorized as high, while the control class obtained 0.70, categorized as medium. Indicator-based analysis showed that the highest improvement occurred in planning a strategy, whereas evaluating the solution remained the weakest indicator. These findings suggest that PhET-assisted problem-based learning effectively improves students’ problem-solving ability in momentum and impulse.